Gambaran hispatologi insang, usus dan otot ikan mujair (Oreochromis mossambicus) yang berasal dari daerah Ciampea, Bogor - B.P. Prisoeryanto .; I.M. Ersa .; R.Tiuria .; S.U. Handayani . (Hemera Zoa, 2010)
The aim of the present study is to describe the histopathological lesions of gill, intestines and muscle tissue of Mujair fish from Ciampea, Bogor. Totally of 30 Mujair fish randomly sampled from 6 different fishpondr in Ciampea, Bogor was used. The observed organs were process for histopathology and stained by Hematoxyln and Eosin. Result of the srudy showed that there were hyperplasia, fusion, oedema, epithelial necroses and metazoan parasitic infestation in gills lamella. Degeneration and cells necroses were commonly found in the tissue muscle; while in the intestines prolifeation of goblet cells and celk necrosis were also common. Based on the result mention above, we concluded that there were several types of histopathological lesions on these three observed organs of Oreochromis mossambicus fish and these lesions were due to infections ofmicrobes andparasite. Poor water quality seemed to play an important role in this case.